Research on the Time-varying Meshing Stiffness Algorithm of Spur Gears Based on an Improved Potential Energy Method - Xu Kejun; Jiao Wei; Qin Haiqin (Jixie chuandong)
Based on the potential energy method, the full tooth profile of the gear teeth is divided into the involute part and the transition curve part, and an improved calculation method for the time-varying meshing stiffness of spur gears is proposed. Using this method, the parametric equation of the tooth root transition curve is considered, and based on the relative size relationship between the radius of the involute starting point, the radius of the base circle and the radius of the root circle, the tooth model with different numbers of teeth is established. A part of the integral upper limit has been corrected to make the gear tooth model more accurate. The time-varying meshing stiffness of gear teeth under different numbers of teeth is calculated, and the calculation results with this method before and after the improvement are compared. The results show that the calculation error caused by the non-coincidence of the starting point radius and the base circle radius of the involute tooth profile will increase with the increase of the number of teeth; when calculating the time-varying meshing stiffness of the teeth with a large difference in the number of teeth, the meshing stiffness calculation should be carried out according to the size of the teeth. There might be a large calculation error when the uniform gear model is used for calculation. Referring to the calculation results of the finite element method, the causes of errors are analyzed, and the effectiveness of the method proposed is verified.